Strategi Penerapan Manajemen Risiko dalam Meminimalisir Kerugian Nasabah di Pasar Berjangka - Damasanti, Tesyalonica Putri; Soebiyantoro, Ugy (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to examine the implementation of risk management strategies to reduce losses experienced by customers in futures trading activities, with a focus on PT Valbury Asia Futures Surabaya Branch. Futures trading has a high level of volatility, potentially causing significant losses if not balanced with adequate risk management. This study uses a descriptive qualitative approach with data collection techniques through direct observation of the company's operational activities, semi-structured interviews with management and financial consultants, and analysis of internal documents related to risk management policies and procedures. The results show that PT Valbury Asia Futures Surabaya Branch has implemented various effective risk management strategies to minimize customer losses. These strategies include the use of stop-loss orders to limit potential losses, the implementation of a margin call mechanism as a form of financial risk control, the implementation of ongoing education for customers through seminars and workshops, and the use of floating profit detection technology that allows for real-time fund withdrawals. Within a six-month period, the implementation of these strategies was able to reduce the level of customer losses by up to 40%. This research finding is in line with the portfolio theory proposed by Harry Markowitz, Albert Bandura's social learning theory, and technological developments in the financial sector. However, the effectiveness of implementing risk management strategies is greatly influenced by the client's level of understanding, discipline, and compliance with the recommendations.